Treatment of metastatic pheochromocytoma and paraganglioma with I-131-meta-iodobenzylguanidine (MIBG) - Kaltsas, G; Mukherjee, J; Foley, R; Britton, K; Grossman, AB (2003)
Pheochromocytomas and paragangliomas (extra-adrenal pheochromocytomas) are relatively rare catecholamine-producing tumors that arise from chromaffin tissue. Radionuclides, such as 131I-meta-iodobenzylguanidine (MIBG), a guanidine derivative, present an imaging modality that has been used for both the diagnosis and staging of chromaffin-cell tumors. Malignant chromaffin-cell tumors account for 10-20% of all cases of chromaffin-cell tumors and show a variable natural history, from a locally invasive indolent tumor to a highly aggressive malignancy. These tumors are best managed by a multidisciplinary team aiming not only at tumor bulk reduction, but also at control of the hypersecretory syndromes resulting from catecholamine excess and maintaining a good quality of life. Surgery with complete resection or debulking of the primary tumor is the treatment of choice, but for disseminated tumors, additional treatment is required. However, systemic chemotherapy has not been shown to be consistently effective, whereas external radiotherapy is mainly reserved for the treatment of localized bony metastases. Pheochromocytomas and paragangliomas that demonstrate positive uptake on a diagnostic 131/123I-MIBG scan can be treated with 131I-MIBG, thus presenting a novel and evolving therapeutic modality in addition to the other traditional therapeutic approaches. In cases with locally aggressive disease, 131I-MIBG therapy is given to complement surgery to help achieve the total eradication of the tumor. In more advanced cases with disseminated disease, 131I-MIBG therapy aims at palliation of symptoms and reduction of tumor function, as well as tumor arrest or even regression after surgery. Treatment with 131I-MIBG is associated with considerable symptomatic and hormonal responses, but fewer patients achieve a tumor response. However, there is stabilization of the disease in the majority with a substantial improvement in the quality of life. 131I-MIBG therapy is safe and well tolerated with minimal adverse effects, although prolonged follow up is still necessary. Although a randomized, controlled study to access the efficacy of 131I-MIBG treatment and its integration with other forms of therapy is awaited, it remains a valuable alternative or additional therapeutic option to the currently available treatment modalities.